Assessing soil nutrient index in mango orchards of Maal area, Lucknow, U.P. - ADAK, TARUN; PANDEY, G.; SINGH, VINOD KUMAR; RAJAN, S. (Journal of Soil and Water Conservation, 2019)
For developing soil nutrient index (SNI), hundred soil samples were collected from root zone depth in hundred mango orchards of villages of Maal region in Lucknow, Uttar Pradesh. Univariate statistics of nutrient data was developed. The SNI in mango orchards of each village was developed and showed that majority of the nutrients were in low to medium ratings. DTPA extractable Zn was low in mango orchards of Thari village while all other orchards had medium ratings. The Cu content showed low while Fe content was medium in orchards of all villages. The Mn content was low in all village mango orchards except Maal village where it showed medium rating. Available K was in medium to high ratings while P was medium in all the orchards. Mango yield in these orchards were <10.0 t ha-1. Yield limiting nutrients indicated need for adoption of good orchard management practices.